Versatile Chip-Scale Lasers : Bridging Near-Ultraviolet to Near-Infrared Spectra (International Journal of Scientific Research in Science and Technology, 2024)
Narrow-linewidth lasers that are widely tunable in the visible spectrum are crucial for various applications such as quantum optics, optical clocks, and atomic and molecular physics. However, current laser systems are typically bulky and confined to laboratory settings, limiting their practical use beyond research environments. In this study, we introduce a chip-scale visible laser platform capable of producing tunable and narrow-linewidth lasers spanning from near-ultraviolet to near-infrared wavelengths. By leveraging micrometer-scale silicon nitride resonators and off-the-shelf Fabry–Pérot laser diodes, we achieve significant coarse tuning capabilities of up to 12.5 nm, coupled with mode-hop-free fine tuning up to 33.9 GHz. Remarkably, our lasers exhibit intrinsic linewidths as low as a few kilohertz. Additionally, our platform demonstrates impressive fine-tuning speeds of up to 267 GHz per microsecond, alongside fiber-coupled powers reaching up to 10 mW and typical side-mode suppression ratios surpassing 35 dB. These remarkable specifications of our chip-scale lasers rival those previously attainable only with large, state-of-the-art benchtop laser systems. This breakthrough positions our lasers as powerful tools poised to drive the next generation of visible-light technologies, enabling practical applications in various fields beyond the confines of traditional laboratory setups.
Keywords: Smart Grid; Chip; Power; Energy